2009
DOI: 10.1785/0120080268
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Two M 5 Mainshocks in Anza, California: Is the Footprint of an Aftershock Sequence Larger Than We Think?

Abstract: It has been traditionally held that aftershocks occur within one to two fault lengths of the mainshock. Here we demonstrate that this perception has been shaped by the sensitivity of seismic networks. The 31 October 2001 M w 5.0 and 12 June 2005 M w 5.2 Anza mainshocks in southern California occurred in the middle of the densely instrumented ANZA seismic network and thus were unusually well recorded. For the June 2005 event, aftershocks as small as M 0.0 could be observed stretching for at least 50 km along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The distance decay exponent is set to 1.9, which is more suitable for triggering of direct aftershocks [ Marsan and Lengliné , ]. Tests with values as small as 1.7 [ Felzer and Kilb , ] gave similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance decay exponent is set to 1.9, which is more suitable for triggering of direct aftershocks [ Marsan and Lengliné , ]. Tests with values as small as 1.7 [ Felzer and Kilb , ] gave similar results.…”
Section: Discussionmentioning
confidence: 99%
“…The large, several weeklong increase in seismicity rates at remote sites suggests that physical processes promoting long‐range earthquake interactions may be operating along this fault. Felzer and Kilb [] studied aftershock sequences triggered by two M ≈5 Anza main shocks that occurred in 2001 and 2005. They concluded that the distribution of aftershocks density as a function of distance to these main shocks followed the typical inverse power law decay observed in southern California and argued that aseismic slip is not required to explain the spatial extent of seismicity.…”
Section: Seismotectonic Backgroundmentioning
confidence: 99%
“…The net scaling could thus range over 0.08 to 8.21 (see Table 1 and Figure 1b). Felzer and Kilb [2009] use p = 1.34 and c = 2 h in their simulations for a southern California M = 5.2 main shock, which would result in a factor of 0.16, much smaller than the value of 1.0 used in their Figure 1. Kagan and Houston [2005] find c = 60 s, and Peng et al [2007] find a c = 20 s, the shortest estimates yet obtained; even for this narrower range, the factor could span 0.66–6.6, too uncertain to argue for continuity in seismicity density decay with distance.…”
Section: Required Rescaling For Figure 1 Of Gomberg and Felzer [2008]mentioning
confidence: 98%
“…However, slow slip has been hypothesized for some time because of observations near Anza, where strainmeter data show anomalies possibly related to slow slip (Agnew & Wyatt 2005) and substantial afterslip at depth following some earthquakes can be inferred from strain and aftershock data (Inbal et al 2013). Furthermore, the moderate earthquakes to the south of Anza are observed to have relatively large aftershock productivity (Felzer & Kilb 2009). High-frequency tremor, which is often observed to accompany slow slip, has also been found near Anza (Gomberg et al 2008;Wang et al 2013).…”
Section: Q Zhang and Pm Shearermentioning
confidence: 99%